STUDENTS’ PERSPECTIVES ON THE IMPLEMENTATION OF MUSICAL ACTIVITIES IN PRESCHOOL EDUCATION - Stramkale, Ligita (Journal of Education Culture and Society, 2018)
Aim. The aim of the study is to find out students’ perspectives on the necessity, readiness and disturbing factors of implementing musical activities in preschool. The theoretical part of the paper describes the particularity of preschool teachers’ work, the children’s interest in musical activities, and the benefits of implementing musical activities in preschool. Method. The empirical study involved 168 students (N=168), of which 132 students (N=132) are already working as preschool teachers in parallel with their study at the university. The study identified three questions: why do preschool teachers use musical activities? What factors prevent a preschool teacher from using musical activities? Is there a relationship between the competence of a preschool teacher in the field of music and the implementation musical activities in preschool? In order to answer the study questions, a questionnaire consisting of twelve statements was created, which had to be assessed on a four-point Likert scale.Results and conclusion. As a result of the analyses of the data obtained in the study, it was ascertained that preschool teachers use musical activities to make children happy and improve their abilities. The use of musical activities is connected with preschool teacher’s willingness to do that. One of the key factors that hinder the implementation of musical activities is an insufficient material base in the preschool. The study also found that there is a correlation between the competence of a preschool teacher in the field of music and the implementation of musical activities.